A USE OF NEW TECHNOLOGY BY ENGLISH TEACHER IN VOCATIOANAL HIGH EDUCATION LEVEL - Wirawan, Fajar; Novita, Loly; Masran, Silviana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to use new technology in English learning at VOCATIONAL HIGH EDUCATION LEVEL. The development of new technology has had a very significant impact on education, especially in increasing effectiveness and motivation in the learning process. The technology used is laptops, mobile phones, voice recorders and projectors. Qualitative descriptive research methods with observation, interviews and documentation were used to collect data. The results of the study indicate that the use of new technology greatly increases students' learning motivation, especially through internet visualization connected via smartphones. However, there are several obstacles, such as unstable internet connections, which are still difficulties that need to be fixed. This study also provides responses to improve the use of new technology more effectively in the English learning process, by paying attention to the use of better new technology in the learning process.